Rapidly developing yeast microcolonies differentiate in a similar way to aging giant colonies - Váchová, Libuše; Hatáková, Ladislava; Cáp, Michal; Pokorná, Michaela; Palková, Zdena (Oxidative medicine and cellular longevity, 2013)
During their development and aging on solid substrates, yeast giant colonies produce ammonia, which acts as a quorum sensing molecule. Ammonia production is connected with alkalization of the surrounding medium and with extensive reprogramming of cell metabolism. In addition, ammonia signaling is important for both horizontal (colony centre versus colony margin) and vertical (upper versus lower cell layers) colony differentiations. The centre of an aging differentiated giant colony is thus composed of two major cell subpopulations, the subpopulation of long-living, metabolically active and stress-resistant cells that form the upper layers of the colony and the subpopulation of stress-sensitive starving cells in the colony interior. Here, we show that microcolonies originating from one cell pass through similar developmental phases as giant colonies. Microcolony differentiation is linked to ammonia signaling, and cells similar to the upper and lower cells of aged giant colonies are formed even in relatively young microcolonies. A comparison of the properties of these cells revealed a number of features that are similar in microcolonies and giant colonies as well as a few that are only typical of chronologically aged giant colonies. These findings show that colony age per se is not crucial for colony differentiation.
Keywords: Ammonia; signální transdukce; Signal Transduction; Yeasts; amoniak; kvasinky